Women's Education, Maternal Health, Entrepreneurship and Development in Nigeria - Dare Ojo OMONIJO1; Sola ALUKO-AROWOLO2; Comfort Oyinlola OYAFUNKE-OMONIYI2; Saheed Akinmayowa LAWAL2; Jonathan A. ODUKOYA3; Elizabeth I. OLOWOOKERE3 (Communications of International Proceedings, 2020)
In modern society, several studies have focused on women affairs in both developed and developing countries. Through some of such studies, some significant improvements have been recorded in the status of women in developed nations while the reverse has been the case in most developing countries such as Nigeria, mostly in the areas of education, maternal health, entrepreneurship and national development. This means women in developing countries are negatively affected in terms of education, maternal health, entrepreneurship and contributions national development in Nigeria. The present paper intends to discuss how women are negatively affected in these areas using data retrieved from a secondary source and content analysis as its methodology. The article used radical feminism theory to gain insight into the plight of women in Nigeria and advocated equal opportunity for men and women to develop their potentials in its concluding remarks. This could go a long way to ensure the transformation of women lives from poverty to affluence and enhance their immense contributions to societal development. Since contributions to national development depend on potentials which do not have any gender connotation, equal opportunity should be granted to male and female for capacity building. Such an effort could greatly enhance national development than when only one gender (male) is solely empowered.
Keywords: Patriarchy; women's education; maternal health; entrepreneurship and development